Functional Characterization of Novel Mutations Affecting Survivin (BIRC5)‐Mediated Therapy Resistance in Head and Neck Cancer Patients. Issue 2 (20th December 2012) - Knauer, Shirley K.; Unruhe, Britta; Karczewski, Sarah; Hecht, Rouven; Fetz, Verena; Bier, Carolin; Friedl, Sandra; Wollenberg, Barbara; Pries, Ralph; Habtemichael, Negusse; Heinrich, Ulf‐Rüdiger; Stauber, Roland H.
<x xml:space="preserve">Abstract</x> Survivin is an acknowledged cancer therapy‐resistance factor and overexpressed in head and neck squamous cell carcinomas (HNSCC). Driven by its nuclear export signal, Survivin shuttles between the nucleus and the cytoplasm, and is detectable in both cellular compartments in tumor biopsies. As predominantly nuclear Survivin is considered a favorable prognostic disease marker for HNSCC patients, we performed laser capture microdissection on corresponding biopsies. Thereby we detected somatic mutations affecting Survivin's nuclear export and thus its cytoprotective activity against chemo‐radiation‐induced apoptosis. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>